PENGGUNAAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES DALAM MENINGKATKAN HASIL BELAJAR KELAS X SMA TBK - Rosanti, Angelica Dwi; Mashudi, Mashudi; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effect of using examples non-examples learning model to increase the students? learning outcomes in the Civic Education Subject. This is an experimental study on the 10th-grade Social 1 Students of SMA Taruna Bumi Khatulistiwa, Kubu Raya Regency. This study was conducted in the form of pre-experimental with one-group pretest-posttest design. 30 students participated in the study. The research instruments used are 20 multiple-choice test items for the pretest and 20 for the posttest. The average scores collected from the pretest and posttest are 53,33 and 77,83. Accordingly, it indicates that there is a difference in the results of students? learning outcomes; therefore, Ho is rejected and Ha is accepted. With the effect size by 1,64 (high category), it is concluded that the applied learning model highly improved the students? learning outcomes in the Civic Education subject at Grade 10 Social 1 SMA Bumi Khatulistiwa Kubu Raya Regency, especially on the material discussing Threat to the state in the frame of Bhinneka Tunggal Ika.Keywords: Civic Education, Example Non Example, Learning Model, Learnig Outcome